2019
DOI: 10.3390/w12010077
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Riparian Vegetation Growth and Sediment Transport Interaction in Floodplain: A Dynamic Riparian Vegetation Model (DRIPVEM) Approach

Abstract: The ecological dynamics of riparian areas interact with sediment transport in river systems, which plays an active role in riparian vegetation growth in the floodplain. The fluvial dynamics, hydraulics, hydro-meteorological and geomorphological characteristics of rivers are associated with sediment transport in river systems and around the riparian area. The flood disturbance, sediment with nutrients and seeds transported by river, sediment deposition, and erosion phenomena in the floodplain change the bare la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 57 publications
0
2
0
1
Order By: Relevance
“…The riparian zone is defined as all stream-adjacent landforms likely to be inundated or saturated by riverine overbank discharges [1]. It delivers dynamic and complex interactions with river channels via bank erosion and sediment deposition (Figure 1), acting as an important structural and functional component of river systems [2][3][4]. More specifically, bank erosion has been recognized as a contributor to suspended sediment load transported by global rivers [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The riparian zone is defined as all stream-adjacent landforms likely to be inundated or saturated by riverine overbank discharges [1]. It delivers dynamic and complex interactions with river channels via bank erosion and sediment deposition (Figure 1), acting as an important structural and functional component of river systems [2][3][4]. More specifically, bank erosion has been recognized as a contributor to suspended sediment load transported by global rivers [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…This zone exhibits unique characteristics, dynamics, and edge effects, making it a critical source of terrestrial and aquatic species, and serving as an essential wildlife habitat. Moreover, the research has demonstrated that the community structure and succession of plants in riparian areas can significantly influence the heterogeneity of hydrological processes [2]. The plants that thrive in riparian areas play an additional distinct role in the landscape through serving as a transitional medium between terrestrial and aquatic ecosystems.…”
Section: Introductionmentioning
confidence: 99%
“…The dam-induced changes in flow regime such as total discharge, shape of seasonal hydrograph, and seasonal and inter-annual variability control many physical and ecological perspectives of river form and processes associated with sediment load, sediment grain size and nutrient transport [2,3]. The dam construction induced drastic alteration of flow regime changes the downstream river morphology in terms of decreases in environmental flow, flow velocity, flow depth, shifting of thalweg, shortage of SS, less erodibility nature of river, and changes in soil particle sizes in the floodplain located at downstream [4][5][6]. These changes in river ecology have negative impacts on downstream aquatic and terrestrial ecosystems [7] and their consequences rely on the purpose of dam construction, the climate inside the catchment, and the policies of the operation of dam gates established on the basis of environmental impact assessment guidelines.…”
Section: Introductionmentioning
confidence: 99%